(3GdCfS GdLdjd HJGQjN GdbOS hGdNdjds - (3YHO GdQMef Hf eMeO Hf YHO GdQMef GdoYndrjej GdMfHdj, nCoHh Gdojref, eLjQ GdOjf,J (B928 (3g` s ((3Ydi Hf YeQ GdYGedi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd Ydi Ndbg HaJM CHhGH GdQMeI CeG HYO agPG eNJUQ GSJNQJ Gddg ai LeYg jJVef JGQjN GdHjJ GdebOSi s
(3BNQgG (B:s
(3hEf aSM Gddg GdGLd LYdJ dg PjdkG CPcQ ajg eG jbY ef GdMhGOK HGdbOS GdTQja hGdMeO ddg hMOg s
(3HChd GdfSNI JeRjb ai HVY ChQGb hHBNQgG bUjOI ai aVd GdbOS GdTQja dYdGA GdOjf Ydi Hf CjhH Hf efUhQ GdebOSi GdTGaYis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B177s
Keywords: (3GdJGQjNs